Assessment of Anti-Cytogenotoxic Effects of Quercetin in Animals Treated with Topotecan. (15th August 2011) - Bakheet, Saleh A.
Abstract : The present investigation was directed to study the possible chemoprotective activity of orally administered quercetin against topotecan-induced cyto- and genotoxicity towards mouse somatic cells in vivo . DNA strand breaks, micronuclei formation, and mitotic activity were undertaken in the current study as markers of cyto- and genotoxicity. Oxidative stress markers such as intracellular reactive oxygen species generation, lipid peroxidation, and reduced and oxidized glutathione were assessed in bone marrow as a possible mechanism underlying this amelioration. Quercetin was neither cytotoxic nor genotoxic in mice at doses tested. Pretreatment of mice with quercetin significantly reduced topotecan-induced genotoxicity and cytotoxicity in bone marrow cells, and these effects were dose dependent. Moreover, prior administration of quercetin ahead of topotecan challenge ameliorated oxidative stress markers. In conclusion, quercetin has a protective role in the abatement of topotecan-induced cyto- and genotoxicity in the bone marrow cells of mice that resides, at least in part, on its antioxidant effects. Based on the data presented, strategies can be developed to decrease the topotecan-induced bone marrow suppression and secondary malignancy in cancer patients and medical personnel exposing to topotecan.